Wannier excitons confined in hexagonal boron nitride triangular quantum dots. (25th January 2023) - Martins Quintela, M F C; Peres, N M R
Abstract: With the ever-growing interest in quantum computing, understanding the behavior of excitons in monolayer quantum dots has become a topic of great relevance. In this paper, we consider a Wannier exciton confined in a triangular quantum dot of hexagonal boron nitride. We begin by outlining the adequate basis functions to describe a particle in a triangular enclosure, analyzing their degeneracy and symmetries. Afterwards, we discuss the excitonic Hamiltonian inside the quantum dot and study the influence of the quantum dot dimensions on the excitonic states.